The Dependence of the International Sensitivity Index on the Coagulometer Used to Perform the Prothrombin Time - Ray, M J; Smith, I R (Thrombosis and Haemostasis, 1990)
This study was designed to detect any effect that different types of coagulation instrument may have on the International Sensitivity Index (ISI) of a thromboplastin.Manufacturers of commercial thromboplastins now calibrate their reagents against the World Health Organization international reference preparation to assign them an IST. This enables the prothrombin time (PT) estimated with that reagent to be expressed as an International Normalised Ratio (INR).One batch of Thromborel S was calibrated against the Australasian Reference Thromboplastin (ART). The Thromborel S was used on three photo-optical instruments, the Automated Coagulation Laboratory (ACL) (Instrumentation Laboratory), the Cobas Fibro (Roche), and the Coag-a-Pet (General Diagnostics). PTs using ART were performed manually using the reference method.The ISIs calibrated in our laboratory when the ACL and Cobas Fibro were used were not significantly different at the 95% level, being 1.102 ± 0.018 and 1.134 ± 0.022 respectively. The ISI with the Coag-a-Pet of 1.223 ± 0.023 was significantly different to that of the ACL and the Cobas Fibro at the 95% level.The flowcharts for a computer program to perform the necessary calculations are provided. The program allows for the entry and editing of data from the calibration procedure, and provides a mean normal PT and normal range, the ISI and 95% confidence limits of the calibration, and a chart for the conversion of the test PTs to INRs.The authors have made available an IBM compatible program for the calibration of thromboplastins.